DEVELOPMENT OF AN SCIENCE LEARNING MODULE BASED ON THE ERP (ENGAGE, RESEARCH, AND PRESENT) LEARNING MODEL TO ENHANCE STUDENTS’ METACOGNITIVE SKILLS - Rondias, Najwa Salsabila; Ismawati, Riva; Muhlisin, Ahmad (Jurnal Pendidikan Matematika dan IPA, 2026)
This study aims to develop a valid, effective, and practical science learning module based on the ERP (Engage, Research, and Present) model to improve students' metacognitive skills. The background of the study was the low metacognitive skills of students at SMP Negeri 5 Magelang, the lack of supporting teaching materials, and learning that does not support independent learning. The study used a Research and Development (R&D) method with the ADDIE development model. The subjects were 31 eighth-grade students. The instruments used included an expert validation sheet, a metacognitive skills test, the Metacognitive Awareness Inventory (MAI) questionnaire, and a student response questionnaire. The results of the study showed that: (1) the learning module was declared valid based on expert validation results with an Aiken’s V score of 0.85; (2) the module was effective in improving students' metacognitive skills, as indicated by the increase in pretest and posttest scores and an N-Gain score of 0.72, categorized as high; and (3) the module was considered practical based on student response questionnaires, with a practicality score of 84.7%, categorized as very practical. The findings indicate that the science learning module based on the ERP model is valid and feasible to be used as teaching material, and it is effective and practical in improving students’ metacognitive skills. The limitations of this study lie in the research design, which did not employ a control group. Therefore, the findings of this study require further investigation.